Effects of mulch and mineral fertilizer on crop, weevil and soil quality parameters in highland banana - Ssali, H.; McIntyre, B.; Gold, C.; Kashaija, I.; Kizito, Fred (2003)
The decline of cooking banana production in parts of East Africa has been associated with a loss of soil fertility and increased pest pressure. Previous work indicated that the use of mineral fertilizers at recommended rates is not financially viable on plantations where pest pressure is high. The objectives of this study were to determine the effects of half the recommended rates of mineral fertilizers and organic mulch on banana yield, soil and foliar nutrient status, soil water and pest damage in the central region of Uganda. The study was conducted in a four-year old banana plantation infested with weevils. Treatments consisted of mineral fertilizer alone, mulch alone, a combination of mulch with fertilizer, and a control (no mulch from outside the plot, or mineral fertilizer applied).2121Fruit yield was generally low (mean of 7.4 Mg ha yr ) and increases above the control ranged from 1.1 to 2.02121Mg ha yr . Banana yield was significantly higher in the sole mulch treatment than in the control. However, there were no significant differences in yield among the treatments that received external inputs. Thus, there was no demonstrable yield advantage of combining mineral fertilizer with mulch. At the end of the trial, soil K concentrations in the two treatments that were mulched, were almost twice those of the control, but this difference was not statistically significant. Concentrations of Ca and Mg did not differ with treatment. Soil available P significantly increased when mineral fertilizer and organic mulch were combined. Treatments that received organic mulch were lower in foliar concentrations of N and Mg, and higher in K. Soil water content was greater in the surface soil layer in the treatments that received mulch, presumably due to less surface run-off and evaporation, since there was no change in surface soil porosity. The effect of organic and inorganic amendments had no impact on weevil damage, which remained above 5% at the end of the trial. We conclude that where weevil damage is over 5% of the cross section near the collar, banana production may not be economically increased through use of either mineral fertilizer and / or organic mulch.